EXPLORING TAX COMPLIANCE BEHAVIOR OF DIGITAL MARKETPLACE ENTREPRENEURS THROUGH THE THEORY OF PLANNED BEHAVIOR - Ahmad Abroza; Kusbianto; Lis Yulitasari; Achlami H.S (Andromeda : Jurnal Manajemen dan Bisnis Syariah, 2025)
The development of the digital economy has given rise to the phenomenon of marketplaces as one of the fastest growing sectors in Indonesia. However, the increase in digital business activity is not always accompanied by optimal tax compliance, posing challenges for tax authorities in expanding the tax base and increasing state revenue. This study aims to explore the tax compliance behavior of digital marketplace businesses using the Theory of Planned Behavior (TPB) as an analytical framework. Data were collected through questionnaires distributed to 63 marketplace businesses with annual turnover below IDR 500 million, using a 1–5 Likert scale. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS. The results show that the three main constructs of TPB, namely attitude, subjective norm, and perceived behavioral control, have a positive and significant effect on intention to comply. Furthermore, intention has a significant effect on actual tax compliance, thus reinforcing the role of intention as a mediator in bridging psychological factors with actual behavior. The R² value of 0.63 for intention and 0.58 for actual compliance indicates that the model used has strong explanatory power in predicting tax compliance. These findings support TPB theory while expanding its application to the context of digital marketplaces, which are still relatively understudied. This study contributes theoretically by strengthening empirical evidence regarding the relevance of TPB in explaining tax compliance behavior in the digital era. From a practical perspective, the results emphasize the importance of building positive attitudes through digital tax literacy, strengthening social norms through marketplace communities, and improving perceptions of control by providing simple and accessible tax service systems. Regulations that encourage the automation of tax collection by marketplace platforms can also be an effective strategy in ensuring actual compliance. Thus, this study not only enriches the taxation literature but also provides relevant policy recommendations for efforts to improve tax compliance in the digital economy sector